Superparamagnetic iron oxide nanoparticles carrying chemotherapeutics improve drug efficacy in monolayer and spheroid cell culture by enabling active accumulation - Nguyen, Khanh; Nuß, Bianca; Mühlberger, Marina; Unterweger, Harald; Friedrich, Ralf P.; Alexiou, Christoph; Janko, Christina (Nanomaterials, 2020)
Cytotoxic and cytostatic chemotherapeutics act by attacking rapidly dividing tumor cells, predominantly affecting malignant tissue and to a certain degree preserving healthy cells. Nonetheless, severe side effects are caused as quickly proliferating healthy cells such as hematopoietic precursors and mucous membranes are impaired as well. This limits the administered dose and eventually allows tumor cells to escape treatment. In order to increase intratumoral drug concentration and simultaneously reduce systemic side effects, nanoparticles have come into focus as drug carriers. The functionalization of superparamagnetic iron oxide nanoparticles (SPIONs) with chemotherapeutics such as mitoxantrone (MTO) enables targeted drug transport by using magnetic forces. Here, we investigate SPIONs consisting of individual iron oxide cores of 10 nm in diameter and a total hydrodynamic diameter of 53 ± 0.8 nm as a transporting system for MTO. Comparing the killing efficacy in monolayer cell culture and multicellular tumor spheroids of HT-29 cells, we show that spheroids tolerate considerably higher doses of nanoparticle-loaded MTO. Therefore, dose predictions from conventional monolayer cell cultures are often misleading for in vivo applications. This was true for both soluble and nanoparticle-bound MTO. Using flow chambers mimicking in vivo blood flow, we furthermore demonstrate that SPIONs can magnetically accumulate MTO. We conclude that SPIONs can function as an effective delivery platform to increase local drug concentrations, thereby potentially overcoming chemotherapy resistance of cells.
CRIS-Team Scopus Importer:2020-09-11
Keywords: Chemotherapy; Drug resistance; Magnetic drug targeting; Mitoxantrone; Nanomedicine; Superparamagnetic iron oxide nanoparticles; Tumor spheroids